Drainage evolution of the Heihe River in western Hexi Corridor, China, derived from sedimentary and magnetostratigraphic results. (15th October 2016) - Pan, Baotian; Chen, Dianbao; Hu, Xiaofei; Cao, Xilin; Chen, Jinjun; Mao, Junwei
Abstract: The uplifting of the Tibetan Plateau has significantly changed the environment in surrounding areas by delivering abundant water and sediment. The Heihe River draining the Qilian Shan in the NE Tibetan Plateau acts as a dominant sediment routing system from the uplifted NE Tibetan Plateau to the Hexi Corridor as well as the Badain Jaran Desert. Reconstructing the evolution of the Heihe River could provide evidence for the birth of the Badain Jaran Desert and enhance the understanding of sedimentary basin fill and the relationship between tectonism, drainage evolution and environmental changes. With this aim, two parallel cores (DWJ and XKJD with depths of 140 and 68.2 m, respectively) were drilled in the floodplain of the Heihe River. The facies analysis of the sedimentary sequences from the drilling cores showed that the sedimentary environment changed from the lake system to a delta system and finally to a fluvial system at the depths of ∼133.3 and ∼68 m, respectively. The magnetostratigraphic results revealed ages of approximately 1.75 and 1.12 Ma for the DWJ and XKJD cores, respectively, and an age of approximately 1.1 Ma for the transition from delta to fluvial environment in both the cores. The change of the sedimentary environment at approximately 1.1 Ma was caused by the formation of the integrated Heihe River. The integrated Heihe River may have developed via mechanisms such as river capture and river diversion due to the uplifting of the North Qilian Shan and the Longshou Shan. The present study suggested that the formation of large inland rivers, such as the Heihe River and the Shiyang River in NW China, played an important role in the evolution of the deserts and the Loess Plateau. Highlights: Present new sedimentological and magnetostratigraphic data from two drill cores in the Hexi Corridor. Reconstructing the evolution of local sedimentary environment and the drainage systems in the western Hexi Corridor. Formation of the integrated modern Heihe River is constrained to be ∼1.1 Ma. Evolution of large rivers in North China impacted the evolution of some largest deserts and the Loess Plateau in China.